Deserters, Traitors and Spies: The Byzantine Approach in the Light of Selected Military Treaties from the 10th Century - Wierzbiński, Szymon (Phantom of Muhammad, Shade of Samuel Byzantine Empire in Relation to Members of Other Cultures and Religions (7th–15th c.): No. XXXIX, 2020)
The main aim of this paper is to define if there was a long lasting and consequent policy toward deserters, traitors and spies in the light of the military treaties from the 10th century (Leo`s Tactica and Sylloge Tacticorum).